No end to war: terrorism in the twenty-first century - Laqueur, Walter (Continuum, 2003)
Roots of terrorism? -- The origins of Islamic terrorism -- Jihad -- Suicide -- Israel and the Palestinians -- Intelligence failure? -- The far right -- Anti-Americanism -- Battlefields of the future 1: India and central Asia -- Battlefields of the future 2: the international brigade -- Conclusion: war against the West